Innovative Urban Design Strategy for Transforming Cities - Grover, Madhur; Gambhir, Vinima; Guruji, V.; Garanayak, Lasyamayee; Thulasiram, Ramachandran; Shukla, Gaurav; Parashar, Komal (AIS - Architecture Image Studies, 2025)
As incubators of innovation, towns and cities have always played a key role in bringing about change and creating surprises. From the Renaissance and Industrial Revolution to the classical Greek and Roman civilizations, comparable occurrences took place in the ancient civilizations of Mesopotamia, the Nile, and the Indus Valley. Cities and towns serve as catalysts for the region's industrialization and modernization as well as for changes in people's lifestyles. In light of the most recent ideas in urban development, the paper supports the importance and necessity of using creative methods in the creation and execution of public policies pertaining to urban renewal. The provisions of each of the selected concepts are analysed in order to present the pertinent ideas for the innovation policy of revitalizing cities. It is concluded that there isn't a single city that has only adopted one of the most recent ideas for urban development. In actuality, we witness the multi-vectorality and amalgamation of urban strategies that eventually supplanted conventional sectoral perspectives. Transforming dilapidated neighborhoods into urban settings that support human life and activities in accordance with the requirements and preferences of their residents is the aim of innovative methods to urban rehabilitation strategy. Both the long-term synergistic impacts on the city as a whole and the impact on a particular degraded area should be taken into account when considering revitalization. It was discovered that human-oriented programs of sustainable area redevelopment lay the groundwork for creative urban revitalization initiatives. The programs are predicated on considering a range of ideas and integrating several activities, particularly: establishment of a small, multipurpose space.